Isolation and characterization of several unique lipids from Azotobacter vinelandii cysts. - Su, C J (1981)
Unique cyclic compounds were found in the lipid fraction of Azotobacter vinelandii cysts. In addition to two major molecular species which had already been identified, 5-n-alkylresorcinol and its galactoside derivative, five other molecular species (two alkyl side chain homologs of each) were isolated, and their structures were established by infrared, ultraviolet, nuclear magnetic resonance, and mass spectroscopy. These 10 compounds were 6-n-heneicosylresorcylic acid methyl ester and 6-n-tricosylresorcylic acid methyl ester, 5-n-(2-hydroxy)heneicosylresorcinol and 5-n-(2-hydroxy-tricosylresorcinol, 5-n-heneicosyl-4-acetylresorcinol and 5-n-tricosyl-4-acetylresorcinol, 6-n-heneicosyl-4-hydroxypyran-2-one and 6-n-tricosyl-4-hydroxypyran-2-one, and 6-(2-oxotricosyl)-4-hydroxy-pyran-2-one and 6-(2-oxopentacosyl)-4-hydroxypyran-2-one.